Cartographie Et Identification Des Activites Sources De Nuisances Et De Pollutions Dans Le Bassin Versant Du Barrage Du Kan De Bouake (Côte d’Ivoire) - Oumar, Fofana; Ahoussi, Kouassi Ernest; Koffi, Avy Stéphane (European Scientific Journal, ESJ, 2017)
This study focuses on mapping and identification of pollution factors in the Kan dam basin in Bouaké (Côte d’Ivoire); All through the use of GIS and field investigations. The consequences of socio-economic development on the Kan dam are important. Indeed, the watershed of the dam appears to be the outlet for all the waters (used and rain) of the town of Bouaké. The mapping of land use in the dam basin allows the identification of nuisance and pollution sources. Mainly five (05) types of nuisance and pollution activities were identified: urbanization (habitat zones); Agriculture (agricultural areas); Fishing (fishing zone); Poultry farming (poultry farming); Cattle breeding (pasture area).